"At Home Camping on Shifting Sands": Lessons in Humility from Between Worlds - Mamtora, Bhakti (Fieldwork in religion, 2020)
This personal narrative analyzes how the practice of intellectual humility can push the boundaries placed around the categories of home and field. I contend that scholars can conduct fieldwork in religion meaningfully by practicing intellectual humility with ourselves, with our interlocutors, and within the academy. Humility with ourselves consists of practicing self-reflexivity and understanding our positionality and its connection to the field. Humility with our interlocutors requires listening to their voices and accepting that fieldwork is dictated by things that happen on the ground and not our neatly conceived plans. Humility in the academy entails an open-minded-ness to theorize about the field from within the field and not necessarily from within the confines of the academy. By practicing intellectual humility, one can begin to bridge the boundaries of home and field, self and other, and become attentive to new directions in academic research.